Early Childhood Caries Experience of Children from Poor Families Living Below and Above Poverty Line - Camila Faria Carrada; Maisa Costa Tavares; Andreia Maria Araújo Drummond; Nagila Maria de Oliveira Correa; Flávio de Freitas Mattos; Rosa Núbia Vieira de Moura; Rosangela Almeida Ribeiro; Saul Martins Paiva (Association of Support to Oral Health Research (APESB), 2021)
Objective: To evaluate the role of poverty and its related factors on early childhood caries (ECC) experience among deprived children. Material and Methods: This population-based cross-sectional study surveyed 418 children aged one to six years enrolled in Brazilian public preschools from an area of the country known for its high social deprivation. Intraoral examination of children evaluated dental caries experience (dmft). Parents/caregivers answered a questionnaire with sociodemographic indicators. Family income was dichotomized into below or above poverty line. Data analysis used Chi-square test, Mann-Whitney test, and Multivariate Logistic Regression analysis (p<0.05). Results: Predisposing variables for an increased chance of ECC were: age group 3-4 years (OR: 4.89; 95% CI: 2.32-10.31), age group 5-6-years (OR: 5.60; 95% CI: 2.60-12.04), being part of families living below poverty line (OR: 1.88; 95% CI: 1.04-3.38) and having mothers with less than nine years of schooling (OR: 2.86; 95% CI: 2.77-7.14). Children from families living below poverty line presented higher dmft (2.9 +3.8; p=0.001) and untreated dental caries (d component) (2.7 +3.7; p=0.002). Conclusion: ECC in a poor population was influenced by indicators of social deprivation. The poorest of poor children from mothers with less years of schooling were at higher risk.